The significance of determining the Intraoperative level of parathormone during surgical treatment of hyperparathyroidism - Janičić Stefan D.; Stepanović Kristina M.; Manojlović Mia S.; Bjelajac Dean P.; Pejaković Slađana M.; Mirković Milan R.; Tomić-Naglić Dragana D.; Bajkin Ivana A.; Ičin Tijana S. (Srpsko lekarsko drustvo, 2024)
Introduction: Surgical treatment is the method of choice for treating primary hyperparathyroidism. Determining parathyroid hormone (PTH) levels intraoperatively allows for real-time monitoring of the functional activity of parathyroid gland tissue and facilitates minimally invasive parathyroidectomy. Aim: Our study aimed to investigate the significance of intraoperative parathyroid hormone level determination in achieving physiological parathyroid hormone levels and cure. Material and Methods: A retrospective academic study analyzed 70 patients from the Clinic for Endocrinology, Diabetes, and Metabolic Disorders at the University Clinical Center of Vojvodina who underwent parathyroidectomy. Participants were divided into control and study groups based on whether intraoperative parathyroid hormone levels were determined. Demographic and laboratory-clinical data from medical records were statistically analyzed. Results: In the study group, the median of parathyroid hormone level was 104.30 pg/mL, while in the control group, it was 128.09 pg/mL; no statistically significant difference was observed (p=0.380). There was no statistically significant difference between groups regarding the number of reoperations indicated and the diagnosis of persistent hyperparathyroidism (p=0.355). A statistically significant difference in treatment outcomes was found among participants who met the Miami and Dual protocol criteria. Conclusion: Determining parathyroid hormone levels during surgical treatment while meeting the criteria of current protocols can contribute to a higher cure rate. A more extensive prospective study is required for a more in-depth analysis of our healthcare center's experience.